Profile of Thyroid Cancer at Dr. Kariadi General Hospital Semarang in 2020 - Sudarmanto, Alif Muhammad; Prajoko, Yan Wisnu; Istiadi, Hermawan; Yudhanto, Eka (http://dharmais.co.id/, 2024)
Background: Thyroid cancer is ranked ninth among the most common type originating from the endocrine glands globally, accounting for approximately 59.7% of cases in Asia. According to 2020 health data, thyroid cancer ranked twelfth in Indonesia, comprising 13,114 cases. Despite the number of cases recorded, there is a lack of comprehensive data regarding the condition of thyroid cancer in the country. Therefore, this research aimed to describe the thyroid cancer profile in Dr. Kariadi General Hospital Semarang.Methods: This descriptive research was carried out using 154 medical records selected through consecutive sampling from Dr. Kariadi General Hospital Semarang from January to December 2020. Categorical scale data were described through frequencies and percentages, while numerical scale data were presented as mean and standard deviation.Results: This research discovered that 57.8% of patients belonged to the 40–59-year-old age group, predominantly consisting of 79.9% females. Additionally, 39.6% of patients had normal thyroid function, with Papillary Thyroid Cancer being the most common type, constituting 92.7% of cases. The results showed that 46.8% of cases were bilateral, 37.7% had a condition of T3, 59.7% had N0, and 89.6% had M0, while 66.2% were classified as stage I.Conclusions: The majority of thyroid cancer patients were 45–64 years old and female. The results showed Papillary Thyroid Cancer as the most prevalent type, with the majority of cases diagnosed at stage I and showing bilaterally presentation. Most of the data correlated with previous research, except thyroid function and histopathology-type percentages.